Pola Pendidikan Karakter dalam Serial Animasi Nussa dan Rarra - Ruslan, Ruslan; Adibah, Aimi (JUPIN (Jurnal Pendidikan Islam Nusantara), 2022)
Basically every parent wants their child to have good and Islamic character in their daily life. However, the current of technological development 4.0 forces parents in particular to be wise in responding to it. This study examines the animated series Nussa and Rarra, how the pattern of character education is in it and how relevant it is to Islamic education in the 4.0 era. For this purpose, this research was carried out using a library approach approach. The data sources used consisted of primary data sources, namely the animated series Nussa and Rarra with the title Ayo Berdzikir, Sleeping Alone, Not Afraid!, Yaah Rain!!!, Yawning Adab, and Love Them. While the secondary data sources are in the form of books relevant to this research. Data collection techniques in this study were observation and documentation. The results show that the animated series Nussa and Rarra is an animation that has a story in the world of children with easy-to-reach language delivery, as a fun child's entertainment, there is also an instillation of character education values ​​that lead to the teachings of Islam. Meanwhile, the pattern of character education in the five animated series Nussa and Rarra are example, habituation/practice, motivation, supervision, and advice. The relevance of Islamic religious education in the 4.0 era is interrelated, where Islamic religious education in the 4.0 era prioritizes character education which can be supported by the use of the Nussa and Rarra animated series in the pattern of character education.